Interpretation and Presentation of Archaeological Sites as a Tool for Creating Bridge between Past and Present: Case of Magnesia on the Meander - Kalfa, Başak; Özgönül, Nimet (ICONARCH International Congress of Architecture and Planning, 2017)
Cultural heritage sites are in increasing demands among people. Developments in advertisement along with the improvements in transportation make these sites more accessible and thrilling. Tools and approaches of displaying cultural and natural heritage sites, in our case archaeological sites, have changed skin eventually to adapt contemporary situation. Nonetheless this change has become insufficient and been in need of revision since the growing interest in archaeological sites enhances audience’s expectations. This condition reveals that new methods of interpretation and presentation should be sought for effective, pleasant and didactic experience. Besides, legislations and charters encourage and even make obligatory to have interpretation and presentation methods in the cultural and natural heritage sites. Especially ICOMOS Charter for the Interpretation and Presentation of Cultural Heritage Sites, known as the Ename Charter (2007) is the most thorough charter on the topic, with its definitions and principles. The interpretation and presentation of archaeological sites is an important asset for an archaeological site to be fully grasped by the visitors and scholars, and sustainably protected for a long period of time. This is mainly because the subject matter represents “the past” in “the present” time and without any interpretation, no one would understand what messages the heritage site has been carrying for centuries. However, interpretation and presentation approach is not enough by itself. Every archaeological site needs a “site management plan” for an integrated and sustainable planning. As it is indicated in charters and legislations, site management plan is the leading authority where interpretation and presentation is a sub-brunch of it. It can be resembled to human structure. If the management plan would be the brain, interpretation would be the skeleton and presentation would be the muscles. They are all creating one body and they cannot operate without each other’s absence. In this paper, a specific case, that is Magnesia on the Meander, will be investigated in the light of the principles of Ename Charter and evaluations will be made for the benefit of proper interpretation and presentation of the site.